2020
DOI: 10.1016/j.msard.2020.102442
|View full text |Cite
|
Sign up to set email alerts
|

Mild clinical manifestations of SARS-CoV-2 related pneumonia in two patients with multiple sclerosis under treatment with ocrelizumab

Abstract: Background: Recently SARS-CoV-2 has spread worldwide causing a pandemic. Little is known about disease severity in immunocompromised hosts and people receiving disease modifying therapies (DMTs). In the last decades DMTs have been widely employed, and ocrelizumab represents one of the newest therapies for the relapsing remitting and progressive forms of multiple sclerosis (MS). Objectives: to describe SARS-CoV-2 related pneumonia in two MS patients under ocrelizumab treatment. Methods: Case series. Results: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
2
19
0
1
Order By: Relevance
“…Dersch et al also described a case of a patient in whom the course of COVID-19 was moderate, even despite severe lymphopenia induced by cladribine [ 25 ]. Similar observations were also made by Maghzi et al and Mantero et al, who described groups of patients with mild COVID-19 who received ongoing DMT, which is in line with other case descriptions in the literature, and the results of the Italian pilot phase of investigation of COVID-19 in patients with MS [ 24 , [28] , [29] , [30] , [31] , [32] , [33] , [34] , 36 , 39 , 40 ]. In March and April 2020, a group of experts from the Section of MS and Neuroimmunology of the Polish Neurological Society (PTN) developed a position on the management of patients with MS using treatment affecting the natural course of the disease in case of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Dersch et al also described a case of a patient in whom the course of COVID-19 was moderate, even despite severe lymphopenia induced by cladribine [ 25 ]. Similar observations were also made by Maghzi et al and Mantero et al, who described groups of patients with mild COVID-19 who received ongoing DMT, which is in line with other case descriptions in the literature, and the results of the Italian pilot phase of investigation of COVID-19 in patients with MS [ 24 , [28] , [29] , [30] , [31] , [32] , [33] , [34] , 36 , 39 , 40 ]. In March and April 2020, a group of experts from the Section of MS and Neuroimmunology of the Polish Neurological Society (PTN) developed a position on the management of patients with MS using treatment affecting the natural course of the disease in case of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…The course of COVID-19 infection is mild in most patients [ 16 , 17 ]. Despite the published case reports, both the risk of infection and the course of COVID-19 in patients with MS are still unclear [ 15 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. It is known that patients with MS are generally more susceptible to infections [ 11 , 37 ], especially those with a higher degree of disability or serious comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Iannetta M et al ( Iannetta et al, 2020 ) reported two patients: a 36-year-old woman with RRMS, EDSS 5.5, and a history of papillary thyroid carcinoma, who was admitted to the hospital due to SARS-CoV-2 infection, but COVID-19 IgG and IgM were undetectable up to 27 days from symptom onset. The other, a 54-year-old with primary progressive MS (PPMS) and EDSS 7 admitted to the hospital due to COVID-19, and IgG became slightly detectable after 28 days from symptom onset.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, given some reports about attenuation of the immune response against COVID in patients on DMTs, there are several questions about the efficacy of possible SARS-CoV-2 vaccine in this group. ( Bollo et al, 2020 ) ( Celius, 2020 ) ( Thornton and Harel, 2020 ) ( Iannetta et al, 2020 )…”
Section: Resultsmentioning
confidence: 99%
“…The best search term with 279 hits turned out to be coronavirus_multiple sclerosis. Finally, all case reports as well as all case series and larger studies which contained information on the different DMTs and the outcome of the respective patients were included [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Methodsmentioning
confidence: 99%